COMPARISON OF GOOD CORPORATE GOVERNANCE DISCLOSURE AND ACHIEVEMENT OF THE MAQASHID SHARIAH BETWEEN INDONESIAN AND MALAYSIAN ISLAMIC BANKS - Ima Maspupah; Shofia Mauizotun Hasanah (AFEBI Islamic Finance and Economic Review, 2018)
As part of the corporate organization, Islamic banks are encouraged to create good performance. But in the benchmark, there are still Islamic banks that assess the performance of banks using conventional measuring instruments. So in this study using maqashid index approach to measure the performance of Islamic banks. In addition to creating good performance, the obligations of business organizations are also to take part in activities aimed at protecting and improving the welfare of society as a whole and creating good corporate governance. banks in Indonesia have poor corporate governance rankings compared to neighboring countries such as Malaysia. So the purpose of this comparison study, it is hoped that there will be some advantages between them that can be identified. The method used in this research is quantitative method by using Mann-Whitney test. The data used are annual reports from three Indonesian islamic banks and three Malaysian Islamic banks. The results obtained no significant differences in Good Corporate Governance between Indonesian and Malaysian Islamic banks. While the achievement of maqashid shariah both have differences. This is because, firstly, the difference between banking history and the second, the difference of implementation of Shariah compliance in both countries.Keywords: Good Corporate Governance, Islamic Banking, Maqashid Shariah